On international law and Gaza: critical reflections - Krever, Tor; Veličković, Marina; Mégret, Frédéric; Engle, Karen; Ní Aoláin, Fionnuala; Knox, Robert; Hammouri, Shahd; Quigley, John; Jaber, Nora; Rigney, Sophie; Kendall, Sara; da Silva, Clare; et al. (Oxford University Press, 2025)
As Israel’s assault on Gaza continues into its tenth month, the language of legality has become the dominant frame of popular and political discourse. Public interest in the International Court of Justice (ICJ) and its proceedings is at a level perhaps never seen before; so too in the International Criminal Court (ICC), its Prosecutor at once urged to act and condemned for inaction, his recent request to judges for the issuing of arrest warrants both celebrated and damned. International law has emerged as the global vernacular of both condemnation and legitimation; few commentators today speak of Gaza or Palestine without invoking the language of il/legality.
What are we to make of this groundswell of interest in and resort to international law?